IoT Water Level Monitoring System - Murugan, Stephanie Lawrencen; Siva Kumar, Leela Thevi; Yani, Achmad; Abdulbaqi, Azmi Shawkat (International Journal of Recent Technology and Applied Science (IJORTAS), 2022)
In the era of globalization today, especially in Malaysia, the Malaysians are often busy with their career and forgot their responsibility to take care the water container or pail at their home which they used to fill water in. This research is designed to solve the problem by detect the level of water inside a container. It also give notification when the container was full. This research also designed to make easier to turn off the water tap whenever the container is filled up. Through this research, it also helps people surrounding to keep them remind about the level of water. The development of this research is using Arduino and Blynk application.